WELFARE INEQUALITY AND DEMOGRAPHIC DIVIDEND IN EAST JAVA: THE OVERLAPPING GENERATIONS (OLG) MODEL APPROACH - Badara Shofi Dana; Ati Musaiyaroh (East Java Economic Journal, 2018)
The issue of demography into an important discussion caused can affect economic growth and inequality in East Java Inequality in east Java showed an increase.Unequal distribution of income is a source of high inequality in East Java. This study aims to show the effectiveness of demographic changes can affect inequality in East Java with the approach of Overlapping Generations (OLG) model. The data used in this research is time series data in the first quarter of 2010- the fourth quarter 2015. Analyzer used in this research is Generalized Method of Moments (GMM). The results of this study show that demographic changes in East Java have the potential to increase inequality. The number of productive age populations with non-productive causes of high inequality. Consumption rate and the number of the productive workforces also become one of the sources of inequality. Therefore, the Settlement of inequality coupled with demographic changes in East Java needs the role of government through targeted social protection programs and infrastructure improvements. In addition, the need for land-based policies, opportunity-based policies, human resource capacity building policies, job matching.